Cyclization vs. Cyclization/Dimerization in o-Amidostilbene Radical Cation Cascade Reactions: the Amide question - Chin , Hui Kee; Ariffin, Azhar; Awang , Khalijah; Ibrahim Ali , Noorbatcha; Takeya, Koichi; Morita, Hiroshi; Chuan , Gee Lim; Thomas, Noel Francis (MDPI, 2011)
The n-butyramido, isobutyramido, benzamido, and furancarboxamido functions profoundly modulate the electronics of the stilbene olefinic and NH groups and the corresponding radical cations in ways that influence the efficiency of the cyclization due presumably to conformational and stereoelectronic factors. For example, isobutyramidostilbene undergoes FeCl3 promoted cyclization to produce only indoline, while n-butyramidostilbene, under the same conditions, produces both indoline and bisindoline.